44‐1: Photo Sensors Embedded within TFT‐LCD with Three Primary Colors Optical Touch Function. Issue 1 (29th May 2019) - Kuo, Chia-Wei; Hung, Ching-Lang; Liao, Yi-Yang; Tsai, Lo-Hsien; Tzeng, Bo-Shiang; Lu, Shao-Ping; Liu, Yu-Jung; Lin, Ching-Huan; Chiang, Min-Feng; Lin, Yu-Chieh; Yu, Jian-Shen
Abstract : In this paper, a 15‐inch XGA TFT‐LCD with embedded 113×256 three primary colors photo sensors is successfully developed by a‐Si:H TFT. Each photo sensor consists of one TFT switch, one storage capacitor and diode‐connected TFTs covered with color filters of three primary colors (red, green, and blue). The diode‐connected TFTs include a recently proposed white‐light photocurrent gating (WPCG) sub‐circuit to suppress the effects of ambient light illumination.